Implementation of School Culture in Forming Student Character at State Elementary Schools - Ahmad Veri Firdaus; Amaliyah Amaliyah; Ariel Adhadila Firmansyah; Nurfadila BT Alizar; Aura Salsabila Putri (EDUJAVARE: International Journal of Educational Research, 2026)
Learning planning is a strategic foundation in the educational process because it allows teachers to organize objectives, materials, methods, media, and evaluation in a targeted manner. This article aims to reconstruct Arabic language learning planning through a synthesis of the systems approach and the humanistic approach. This study uses library research methods with a conceptual approach and descriptive-critical analysis. The results of the study indicate that the systems approach remains important as a structural foundation for Arabic language learning planning, but has limitations when used alone because it tends to be technical and administrative, and less sensitive to the individual needs of learners. Meanwhile, the humanistic approach contributes to placing learners at the center of learning, paying attention to affective and psychological aspects, and encouraging more adaptive, participatory, and meaningful learning. Based on this, this article offers a conceptual model for humanistic-system-based Arabic language learning planning, which includes analysis of student needs, formulation of integrative objectives, systematic and contextual organization of materials, selection of adaptive methods and media, implementation of participatory learning, and comprehensive and reflective evaluation. In conclusion, the reconstruction of humanistic-system-based Arabic language learning planning produces a more complete planning paradigm, namely remaining systematic but simultaneously oriented towards holistic student development.